EFFECT OF BASE REINFORCEMENT ON THE BEHAVIOR OF EMBANKMENT OVER SOFT SUBSOIL - C. W. Yang; J. C. Chai; N. Miura; Y. S. Ye (Lowland Technology International, 1999)
A case history of both reinforced and unreinforced embankments on soft subsoil built to failure is described. The results of a laboratory model test about the behavior of embankment on soft soil are referred during discussions. The effect of geotextile reinforcement on embankment behavior is discussed by comparing the field data of with and without reinforcement cases. The field data as well as analysis indicate that the reinforcement had a certain effect on embankment stability. However, at working state (normally with a factor of safety of 1.2 to 1.3), the reinforcement did not have an obvious effect on subsoil response. Only under the condition that unreinforced embankment approached to failure, the effect of reinforcement on subsoil could be noticed. The laboratory model test results indicated that if the reinforcement is strong enough, the effect of reinforcement is considerable. It is suggested that although the geotextile certainly has a beneficial effect on embankment over soft subsoil, due to the relative lower stiffness of geotextile, to achieve a substantial improvement on embankment behavior, the multi-layer geotextile reinforcements or high strength geogrid may be needed. This case history also demonstrated that the rate of lateral displacement and excess pore pressure development are sensitive indexes for the stability of embankment on soft subsoil.